From Informal to Formal Finance: The Transformation of an Indigenous Institution in Nepal - Hans Dieter Seibel; Heiko Schrader (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1999)
Rotating savings and credit associations (RoSCAs) are, next to moneylenders, the most prevalent type of informal finance around the world. In 1988, Seibel & Shrestha traced the evolution of the dhikuti, as RoSCAs are called in Nepal, and published the results under the title Dhikuti: The Small Businessman?s Informal Self-Help Bank in Nepal in Savings and Development (XII, 2:183-200). Ten years later, a remarkable institutional innovation had occurred, benefiting from a change in the legal framework: the transformation of an organization of dhikuti origins into the Himalaya Finance & Savings Company. No subsidy or technical assistance was involved. HFSC provides doorstep savings collection services to low-income people throughout the country, shifting at the same time from group to individual technology. Matching assets and liabilities, it combines two categories of term finance: medium-term savings contracts and medium-term loans. Continuing its morphogenesis, HFSC is now ready to transform itself into a bank and to pursue an even more vigorous course of internal resource mobilization. – – La tontine, ? côté du pr?teur d'argent, est le type de finance informelle le plus répandu au monde. En 1988, Seibel et Shrestha ont tracé l'évolution des dhikuti, les tontines Népalaises, et ont publié le résultat sous le titre Dhikuti: The Small Businessman's Informal Self-Help Bank in Nepal dans Savings and Development (XII, 2:183-200). Dix ans apr?s, une innovation institutionelle remarquable a eu lieu, grâce ? un changement du cadre juridique: la transformation d'une organisation d'origine dhikuti en Himalaya Finance & Savings Company, et cela sans avoir reçu ni de subventions ni d'assistance technique. Partout dans le pays, HFSC collecte quotidiennement de l'épargne des pauvres ? leurs maisons, changeant en m?me temps de la technologie de groupe ? une approche individuelle. Deux catégories de financement ? terme ont étées combiné pour équilibrer l'actif et le passif: des contrats d'épargne de trois ans et des pr?ts d'un ? trois ans. En continuant le proc?s d'évolution, la compagnie financi?re se prépare maintenant ? se transfomer en une banque pour suivre un cours de mobilisation d'épargne encore plus vigoreux.
Keywords: 330; Informeller Finanzsektor; Nepal